Aspects of Islamic Education - Anisa Khairani; Nazwa Azzahra Sahusilawane; Indah Permata Sari Pasaribu (Journal of Contemporary Islamic Primary Education, 2024)
Education is very important for human because education is a very wide knowledge. So, Islamic education not only looking to one aspect, its aspects of faith, worship, and morals, but its almost a whole thing and even wider than that. This article aims to analyze the aspects of Islamic education. The method that used in this writing is the literature study method, which is the data collection method is directed at finding data and information through documents, written documents, images, and electronic documents that can support the writing process. The results of the study show that the aspects of Islamic education are interrelated and form an integrated system based on the Qur'an and Sunnah as well as the opinions of the scholars who aim to form collective piety and have a noble goal, to create good and kind humans and have quality in the spiritual-religious and intellectual.